2016
DOI: 10.1002/ejic.201501284
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Fluorescence Properties of ortho‐Carbor­anes: Unusual Emission Behaviour in C‐(2′‐Pyridyl)‐ortho‐carboranes

Abstract: Seventeen compounds including the parent ortho-, meta-and para-carboranes and derivatives of ortho-carborane were investigated for luminescence in cyclohexane and dichloromethane solutions. Fifteen of these carboranes revealed very weak emissions in the 285-493 nm range. These carboranes may arguably be viewed as non-emissive in solutions at room temperatures. No emissions could be observed for 1,2-dimethyl-ortho-carborane and 2-methyl-1-phenyl-ortho-carborane. The carboranes with a 2′-pyridyl substituent at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 150 publications
(108 reference statements)
0
29
0
Order By: Relevance
“…Fox et al have also reported C ‐diazaboryl‐ o ‐carborane dyads ( II ) exhibiting dual emissions from high‐energy LE and low‐energy CT states, depending on the substituents and molecular geometry , . Furthermore, o ‐carborane derivatives ( III ) with 2‐pyridyl or diphenylphosphino groups displayed multiple‐emission features via different excited states . Recently, we reported that a biphenylene‐bridged dimeric o ‐carboranyl triarylborane compound ( IV ) can show dual emissions, resulting from a triarylborane‐based LE and an ICT‐based aggregation‐induced emission (AIE) in a rigid state.…”
Section: Introductionmentioning
confidence: 85%
“…Fox et al have also reported C ‐diazaboryl‐ o ‐carborane dyads ( II ) exhibiting dual emissions from high‐energy LE and low‐energy CT states, depending on the substituents and molecular geometry , . Furthermore, o ‐carborane derivatives ( III ) with 2‐pyridyl or diphenylphosphino groups displayed multiple‐emission features via different excited states . Recently, we reported that a biphenylene‐bridged dimeric o ‐carboranyl triarylborane compound ( IV ) can show dual emissions, resulting from a triarylborane‐based LE and an ICT‐based aggregation‐induced emission (AIE) in a rigid state.…”
Section: Introductionmentioning
confidence: 85%
“…One promising platform to overcome the ACQ problem is a class of aggregation-induced emission (AIE)-active boron complexes, which show significant emission not in the dilute state but in aggregation. [22][23][24][25][26][27][28][29][30][31][32][33][34] We have also focused on the arylmodified o-carboranes as a scaffold for constructing luminescent "element-block", [35,36] which is defined as a minimum functional unit composed of heteroatoms. [4] Additionally, based on environment-responsive intensity changes of the AIE-active materials, various types of film-type luminescent materials and sensors can be fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a more stable radical species was observed for the one‐electron chemical reduction of 1,2‐diphenyl‐ ortho ‐carborane, 1,2‐Ph 2 ‐1,2‐C 2 B 10 H 10 ( 1 , Figure ) , . Such one‐electron reductions were not found for 12‐vertex parent carboranes or for carborane derivatives without aryl group(s) attached to the cluster carbon atom(s) , . While carborane radicals with 2 n +1 and 2 n +5 SEs are also known, this investigation looks at carborane radicals with 2 n +3 SEs.…”
Section: Introductionmentioning
confidence: 99%
“…There are now several 12‐vertex 2 n +3 dicarbaborane radicals known with different aryl and heteroaryl groups attached to the cluster carbon atom(s) with varying degrees of stability , , . This is not surprising, as the stable and commercially available 12‐vertex dicarbaboranes (carboranes) are widely researched.…”
Section: Introductionmentioning
confidence: 99%